The 5Ws of Racial Equity in Research: A Framework for Applying a Racial Equity Lens Throughout the Research Process (Mary Ann Liebert, 2022)
Ensuring equity in research is a critical step in advancing health equity. In this perspective, the authors introduce a guiding framework for advancing racial equity in research processes, environments, and among the research workforce, the 5Ws of Racial Equity in Research. Centering their discussion on the 5Ws: Who, What, When, Where, and Why, they use historical and contemporary examples of research inequities to demonstrate how these five simple questions can encourage open discussion and proactive planning for equity in research. They close with an acknowledgment of the framework's broad utility and a researcher-directed call to action.